Acute care practices relevant to quality end-of-life care: a survey of Pennsylvania hospitals. Issue 6 (27th April 2010) - Lin, C Y; Arnold, R M; Lave, J R; Angus, D C; Barnato, A E
Abstract : Background: Improving end-of-life care in the hospital is a national priority. Purpose: To explore the prevalence and reasons for implementation of hospital-wide and intensive care unit (ICU) practices relevant to quality care in key end-of-life care domains and to discern major structural determinants of practice implementation. Design: Cross-sectional mixed-mode survey of chief nursing officers of Pennsylvania acute care hospitals. Results: The response rate was 74% (129 of 174). The prevalence of hospital and ICU practices ranged from 95% for a hospital-wide formal code policy to 6% for regularly scheduled family meetings with an attending physician in the ICU. Most practices had less than 50% implementation; most were implemented primarily for quality improvement or to keep up with the standard of care. In a multivariable model including hospital structural characteristics, only hospital size independently predicted the presence of one or more hospital initiatives (ethics consult service, OR 6.13, adjusted p=0.02; private conference room in the ICU for family meetings, OR 4.54, adjusted p<0.001). Conclusions: There is low penetration of hospital practices relevant to quality end-of-life care in Pennsylvania acute care hospitals. Our results may serve to inform the development of future benchmark goals. It is critical to establish a strong evidence base for the practices most associated with improved end-of-life care outcomes and to develop quality measures for end-of-life care to complement existing hospital quality measures that primarily focus on life extension.